Development of a finger biomechanical model - Foo, Boon Kiat. (2011)
Forces in hand tendons due to various hand functions have been of great interest to surgeons and researchers. The knowledge on tendon forces could help surgeons to restore patient’s tendon during rehabilitation period. This leads to the development of this project which is to determine the tendon forces at the wrist due to various hand functions.